Dūrum and Uruk During the Ur III Period - Michałowski, Piotr
ersch. 1978; copies AUAM (Archeological Museum of the Andrews University Seminary) 73.0448, HSM 911.3.108, 911.10.556, 911.10.556 (sic), 911.10.132; BÀD.ANKI.